Anisotropic Fermi couplings due to large unquenched orbital angular momentum: Q-band (1)H, (14)N, and (11)B ENDOR of bis(trispyrazolylborate) cobalt(II). - Myers, W; Scholes, C; Tierney, D (2009)
We report Q-band ENDOR of (1)H, (14)N, and (11)B at the g( parallel) extreme of the EPR spectrum of bis(trispyrazolylborate) cobalt(II) [Co(Tp)(2)] and two structural analogs. This trigonally symmetric, high-spin (hs) S = 3/2 Co(II) complex shows large unquenched ground-state orbital angular momentum, which leads to highly anisotropic electronic g-values (g( parallel) = 8.48, g( perpendicular) = 1.02). The large g-anisotropy is shown to result in large dipolar couplings near g( parallel) and uniquely anisotropic (14)N Fermi couplings, which arise from spin transferred to the nitrogen 2s orbital (2.2%) via antibonding interactions with singly occupied metal d(x(2)-y(2)) and d(z(2)) orbitals. Large, well-resolved (1)H and (11)B dipolar couplings were also observed. Taken in concert with our previous X-band ENDOR measurements at g( perpendicular) ( Myers, W. K.; et al. Inorg. Chem. 2008, 47, 6701-6710 ), the present data allow a detailed analysis of the dipolar hyperfine tensors of two of the four symmetry distinct protons in the parent molecule. In the substituted analogs, changes in hyperfine coupling due to altered metal-proton distances give further evidence of an anisotropic Fermi contact interaction. For the pyrazolyl 3H proton, the data indicate a 0.2 MHz anisotropic contact interaction and approximately 4% transfer of spin away from Co(II). Dipolar coupling also dominates for the axial boron atoms, consistent with their distance from the Co(II) ion, and resolved (11)B quadrupolar coupling showed approximately 30% electronic inequivalence between the B-H and B-C sp(3) bonds. This is the first comprehensive ENDOR study of any hs Co(II) species and lays the foundation for future development.